PHYSICAL EXERCISE TO IMPROVE HEALTHY LIFESTYLES - Sultonov Usmon Ibragimovich; Saruxanov Arsen Albertovich; Ochilova Khursanoy Muminjonovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The relevance of the problem of forming a healthy lifestyle of students is determined by the fact that most students lose the understanding that self–development, having healthy lifestyle skills is a help not only to themselves, but also to others. Modern conditions of educational activity in universities place increased demands on the state of health of students. Motor activity with a wellness orientation is currently considered as the main, and sometimes the only way to form and maintain health.